Automotive control systems - Ulsoy, Ali Galip; Peng, Huei.; Cakmakci, Melih (Cambridge : Cambridge University Press, 2012)
'This engineering textbook is designed to introduce advanced control systems for vehicles, including advanced automotive concepts and the next generation of vehicles for ITS. For each automotive control problem considered, the authors emphasize the physics and underlying principles behind the control system concept and design. This is an exciting and rapidly developing field for which many articles and reports exist but no modern unifying text. An extensive list of references is provided at the end of each chapter for all the topics covered. It is currently the only textbook, including problems and examples, that that covers and integrates the topics of automotive powertrain control, vehicle control and intelligent transportation systems. The emphasis is on fundamental concepts and methods for automotive control systems, rather than the rapidly changing specific technologies. Many of the text examples, as well as the end-of-chapter problems, require the use of MATLAB and/or SIMULINK'--
'The century old automobile, the preferred mode for personal mobility throughout the developed world, is rapidly becoming a complex electro-mechanical system. Various new electro- mechanical technologies are being added to automobiles to improve operational safety, reduce congestion and energy consumption and minimize environmental impact. This chapter provides an introduction to these trends, as well as a brief overview of the major subsystems of an automobile and a brief overview of the automotive control systems to be described in detail in subsequent chapters'--
Machine generated contents note: Preface; Part I. Introduction and Background: 1. Introduction; 2. Automotive control-system design process; 3. Review of engine modeling; 4. Review of vehicle dynamics; 5. Human factors and driver modeling; Part II. Powertrain Control Systems: 6. Air-fuel ratio control; 7. Control of spark timing; 8. Idle speed control; 9. Transmission control; 10. Control of hybrid vehicles; 11. Modeling and control of fuel cells for vehicles; Part III. Vehicle Control Systems: 12. Cruise and headway control; 13. Antilock brake and traction-control systems; 14. Vehicle stability control; 15. Four wheel steering; 16. Active suspensions; Part IV. Intelligent Transportation Systems: 17. Overview of intelligent transporation systems; 18. Preventing collisions; 19. Longitudinal motion control and platoons; 20. Automated steering and lateral control; Appendix A. Review of control-theory fundamentals; Appendix B. Two-mass three degree of freedom vehicle lateral/yaw/roll model; Index.
Includes bibliographical references and index.
Keywords: Automobiles -- Automatic control; Adaptive control systems; Automobiles -- Motors -- Control systems